Indigenous Community-Based Cultural Tourism Communication - Andung, Petrus Ana; Letuna, Mariana A. Noya; Nara, Maria Yulita; Leuape, Emanuel Sowe (Jurnal Komunikasi, 2023)
Kampung Adat Ratenggaro (KAR) is a unique cultural tourism destination in Southwest Sumba Regency (SBD). This traditional village, which is located in the village of Maliti Bondo Ate, has traditional house buildings with quite unique shapes, historical tours in the form of stone graves, and Ratenggaro Beach natural attractions. This attraction makes many tourists come to visit the Ratenggaro Traditional Village. KAR tourism is now fully managed by indigenous peoples. This study aims to map the tourism communication model developed through the active involvement of indigenous peoples. This study is qualitative research using a case study approach. The study shows that the tourist destinations contained in the KAR highlighted the concept of tourism based on local branding by utilizing the local wisdom of the local community. Meanwhile, the involvement of local communities in KAR's tourism activities can be seen starting from tourism planning, and tourism promotion, to evaluation. The tourism communication model developed by KAR is based on indigenous peoples by placing the role of ndorumbaha (local tour guide) as a central figure in KAR tourism. Ndorumbaha is an essential figure in conducting KAR tourism communication. The ndorumbaha is tasked with conveying various information about what and how each KAR tourist attraction is to every visitor, both domestic and foreign. This tourism communication model in turn will be able to guarantee the creation of sustainable tourism with prominent local branding.